Penggunaan Paylater Sebagai Metode Pembayaran Uang Kuliah Tunggal Oleh Mahasiswa Dalam Perspektif Maslahah - Wahyudi, Ahmad Zulfi; Alfikri, Ahmad Faiz Shobir; Sumidartini, Ai Netty (Perbanas Journal of Islamic Economics and Business, 2025)
This study aims to analyze the legality of the use of paylater as a method of paying the Single Tuition Fee (UKT) based on the applicable legal review. This research also aims to evaluate the maslahah aspects resulting from the application of this payment method by students. The novelty of this research lies in the analysis that connects the use of paylater as a UKT payment method by students with a maslahah perspective, which has never been studied in the previous literature. This research is normative legal research with a statute and conceptual approach. The result of this research is that the use of paylater to pay UKT has legality based on OJK regulations but has not been explicitly regulated in the education sector. The paylater agreement must fulfill Article 1320 of the Civil Code. Synchronizing fintech and education regulations is a challenge that must be resolved. From a maslahah perspective, paylater supports education and financial management (hifz al-‘aql and hifz al-mal) if following sharia, but risks becoming maslahah mulgah if not wise. Paylater can be categorized as anemergency (darurat) if there is no other alternative to pay UKT, or an important need (hajat) if it is used to ease the payment burden in the short term. However, at the tahsînat level, paylater is more optional and must be used wisely. The implication of this research is to encourage policy harmonization between OJK and the Ministry of Education and Science to ensure that the use of paylater in the education sector runs according to the principle of maslahah, supports access to education, protects consumers, and avoids practices that have the potential to burden students financially.